Prospek Masa Depan Timor Timur - Ganewati Wuryandari (Jurnal Masyarakat dan Budaya, 1999)
Timor Timur (East Timor) has been a longtime problem for Indonesia and for its people. This caused by the process of become Indonesia part was not so simple. The Indonesia government is not aware about this situation. In developing effort of this new province, the government of Indonesia has not been paying attention to the social and cultural aspects of the local people. It seems that those people have been exploited and their right as humans was also been violated